Impact of open femoral endarterectomy on treating multilevel iliac and common femoral artery occlusive disease - Park, Suehyun; Ku, Taewan; Hwang, Deokbi; Yun, Woo-Sung; Huh, Seung; Kim, Hyung-Kee (Frontiers in Surgery, 2025)
PurposeThis study aimed to evaluate the impact of femoral endarterectomy (FE) on treating multilevel iliac and common femoral artery occlusive disease.Materials and methodsFrom January 2013 to December 2022, 106 limbs in 103 patients with multilevel arterial occlusive disease underwent open FE and iliac angioplasty (FEIA) with or without infrainguinal revascularization. The primary outcome assessment was the changes in the TransAtlantic Inter-Society Consensus (TASC) II classification during the operation; the secondary outcomes included the primary patency (PP) and secondary patency (SP) of FEIA. The risk factors for PP loss were evaluated.ResultsOf the 103 patients, 91 were male. A total of 56 limbs were treated for chronic limb-threatening ischemia, and 61 limbs underwent infrainguinal revascularization. Preoperatively, aortoiliac occlusive disease (AIOD) was classified as TASC II C in 65 (61%) limbs and D in 41 limbs. During the operation, 19 limbs received additional thrombectomy for subacute or chronic thrombus components. Overall, FE and additional thrombectomy reduced the TASC II classification of AIOD from complex lesions (TASC II C/D) to simple lesions (B or lesser) in 101 (95%) of 106 limbs. Three early mortalities (2.8%, two from acute myocardial infarctions and one from pneumonia) were recorded. The PP and SP of FEIA were 89% and 96% at 1 year, 80% and 94% at 3 years, and 77% and 94% at 5 years, respectively. The severity of iliac and common femoral artery disease was not associated with PP loss of FEIA.ConclusionsDespite the challenging nature of initially classified TASC II C/D lesions, our findings highlight the effectiveness of FE in reducing TASC II classification and the durable patency achieved with FEIA. Hybrid FEIA could be a viable primary treatment option, particularly for lesions featuring severe iliac and common femoral artery disease.